2016
DOI: 10.5194/hess-20-2759-2016
|View full text |Cite
|
Sign up to set email alerts
|

Redox controls on methane formation, migration and fate in shallow aquifers

Abstract: Abstract. Development of unconventional energy resources such as shale gas and coalbed methane has generated some public concern with regard to the protection of groundwater and surface water resources from leakage of stray gas from the deep subsurface. In terms of environmental impact to and risk assessment of shallow groundwater resources, the ultimate challenge is to distinguish (a) natural in situ production of biogenic methane, (b) biogenic or thermogenic methane migration into shallow aquifers due to nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…Figure shows a plot of SO 4 versus DOC and includes the concentrations of methane in each sample depicted with symbols in three colors. Methane concentrations increase with increasing DOC and decreasing sulfate concentrations that typify reducing conditions and are consistent with the methane originating as microbial gas from shallow in situ production in the aquifer (Humez, Mayer, Nightingale, et al, ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Figure shows a plot of SO 4 versus DOC and includes the concentrations of methane in each sample depicted with symbols in three colors. Methane concentrations increase with increasing DOC and decreasing sulfate concentrations that typify reducing conditions and are consistent with the methane originating as microbial gas from shallow in situ production in the aquifer (Humez, Mayer, Nightingale, et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…These elevated gas concentrations may pose a threat to public safety from explosions, groundwater contamination, and impaired air quality (Chilingar & Endres, ; Eltschlager et al, ; Vidic et al, ). Sources of methane in groundwater commonly include the accumulation of methane from in situ microbial production, for example, (Beeman & Suflita, ; Humez, Mayer, Nightingale, et al, ) or the migration of thermogenic oil field gases toward the surface along faults or as a result of well‐integrity failure in poorly completed or abandoned oil wells, for example (Breen et al, ). Incidents related to gas seeps and gas migration from oil field operations or storage facilities have resulted in methane gas release, explosions, loss of life, and extensive damage to property, including the 24 March 1985 Ross Department Store explosion in the Fairfax district of Los Angeles California (Chilingar & Endres, ; Jenden, ; Schoell et al, ) and the 17 January 2001 explosion and fires that destroyed most of downtown Hutchinson Kansas (Allison, ), and in 2013, a water well in Hawthorne, CA, began leaking water and methane, requiring the evacuation of 37 nearby homes, and the shutdown of the surrounding freeways, before it was plugged (Jennings, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the absence of higher molecular weight gaseous alkanes in the majority of the water samples ( n = 11) did not support this hypothesis [C 1 /(C 2 + C 3 ) > 1,000; Figure 1B]. The heavy isotopic signature of methane, sampled at the same time as samples for microbial community analysis, coupled with the absence of C 2 and C 3 gases indicated that biogenic methane has likely undergone oxidation in most of the aquifers sampled (Humez et al, 2016). The isotope signature of methane therefore, probably has been influenced by the microbial activity and the proportion of biogenic methane may be underestimated owing to the oxidation of methane (Barker and Fritz, 1981).…”
Section: Discussionmentioning
confidence: 98%
“…It is worth noting that heating of soil and underlying strata by thermal operations in this area likely accelerate bacterial activity (Madigan et al, 2003), hence the occurrence of biogenic methane. In central and southern Alberta, besides gas of biogenic origin, coal gas originating in the many coal seams above the Colorado Group has been identified in a significant number of water samples (Humez et al, 2016). To conclude, in the great majority of cases the gas migrating outside well casing does not originate in the production reservoir, but in overlying strata, particularly organic rich shales and coal beds.…”
Section: Gas Sourcementioning
confidence: 98%
“…Because gas migrating to the surface outside well casing is not easy to capture, several isotopic studies on GM in Alberta and western Saskatchewan (20 km east of Lloydminster) have focused on gas found in shallow groundwater aquifers, gas captured at surface casing vents and gas found in mud samples from newly drilled wells (Rowe and Muehlenbachs, 1999a;Szatkowski et al, 2002;Muehlenbachs, 2006, 2011;Humez et al, 2016). Methane mostly of biogenic origin is ubiquitous in shallow groundwater aquifers, hence also in the overlying vadose zone and soils.…”
Section: Gas Sourcementioning
confidence: 99%